Genetic identification of purebred and crossbred water buffalo [Bubalus bubalis (linnaeus, 1758)] in selected farms in Malaysia - Shaari, Nor 'Ammar Liyana (2019)
Water buffalo or Bubalus bubalis is a domesticated animal that plays essential roles in agriculture, economy and food production. Water buffalo is classified into two sub- species based on the phenotypic, genotypic and cytogenetic. The two subspecies of water buffalo is murrah buffalo (Bubalus bubalis bubalis) and swamp buffalo (Bubalus bubalis carabensis). Identification based on morphology is not enough to confirm the species or to make the comparison between the two sub-species. The problem arises when these two sub-species mates and produce their crossbreed offspring, which is indistinguishable from their parents. Therefore, the aim of this study is to determine three sub-species of water buffalo available in Pusat Ternakan dan Pembiakan Kerbau, Telupid, Sabah and Ladang Ternakan Kerbau Semenyih (Semenyih Farm) using karyotyping and molecular methods. In addition, phylogenetic analysis is to determine the differences in the nucleotide sequences, associated with the relationship evolutionary events between species. The blood of 112 animals were taken, cultured, terminated and harvested using conventional karyotyping protocol to obtain the chromosomes. Results showed that from 112 buffaloes in PLadang Ternakan dan PembiakanHaiwan, Telupid, Sabah, 97 animals successfully identified were confirmed as swamp buffalo presented with 48 chromosomes and the remaining 7 were identified as crossbred buffalo presented with 49 chromosomes. However, in Semenyih Farm, 8 animals were successfully identified as murrah buffalo presented with 50 chromosomes. In molecular work, the bloods were collected and the PCR were conducted to quantify the d-loop of mitochondrial DNA in three sub-species. Two pairs of primers known as NP1 and NP2 were designed to amplify the full d-loop region by PCR. The purified PCR products from three sub-species were then sent for sequencing. Results from sequencing showed that the full d-loop of mitochondrial DNA is successfully amplified, consist of 1000 base pairs. Based on the multiple sequence analysis, the three subspecies of water buffalo shared many conserve region and they also showed some differences in their nucleotide sequences. The mean molecular weight (Da) is also differ each sub-species, which swamp with 343,747.70 Da, crossbreed with 345,331.30 Da and murrah with 335,374.22 Da. All d-loop mitochondrial DNA sequences from this study hit the NCBI blast for the most similar sequences with 99% identical to the sequences available from the database. Phylogenetic tree was constructed using maximum likelihood analysis using software MEGA 7.0. From the phylogenetic results, the swamp and murrah clearly formed two different clades, showing that they are diverged from each other. On the other hand, crossbreed buffalo is claded into the swamp buffalo, showing that swamp buffalo is more dominant in the crossbreed compared to murrah buffalo. By combining karyotyping method, molecular study and also phylogenetic tree, the result obtained from this study is more convincing and complete compared to analysis done solely on one aspect. In conclusion, the genetic identification is crucial in identifying the three sub-species of water buffalo, as it can provide more concrete and clear result compared to conventional method such as morphological analysis.